Do Motivation and Competence Influence the Performance of Teachers in Vocational Schools? - Septin, Angel Chandra; Rumijati, Aniek; Febriani, Rizki (University of Muhammadiyah Malang, 2024)
Teacher performance in Indonesia is like a complex phenomenon, combining bright and shadowy sides. Many teachers in Indonesia still need to improve their qualifications and competencies. This study aims to analyze the influence of motivation and competence on teacher performance and career development as mediating variables. This research was conducted on Telkom Malang Vocational School teachers, with 71 teachers as respondents. The sampling technique uses saturated sampling or census. Data collection was carried out using questionnaire techniques. The data analysis technique uses the PLS-SEM method with SmartPLS software. The results showed that motivation did not significantly affect teacher performance or career development. Conversely, competence positively and significantly influences teacher performance and career development. However, career development does not affect teacher performance. In addition, motivation does not affect teacher performance through career development, and competence does not affect teacher performance through career development. There is a need to focus on developing teacher competencies to improve their performance and career. Motivation may not be a key factor, but it is vital to maintain adequate motivation in a work environment.